Activated T cells enhance interferon-α production by plasmacytoid dendritic cells stimulated with RNA-containing immune complexes. Issue 9 (22nd October 2015) - Leonard, Dag; Eloranta, Maija-Leena; Hagberg, Niklas; Berggren, Olof; Tandre, Karolina; Alm, Gunnar; Rönnblom, Lars
Abstract : Objectives: Patients with systemic lupus erythematosus (SLE) have an ongoing interferon-α (IFN-α) production by plasmacytoid dendritic cells (pDCs). We investigated whether T cells can promote IFN-α production by pDCs. Methods: Human pDCs were stimulated with immune complexes (ICs) containing U1 small nuclear ribonucleic proteins particles and SLE-IgG (RNA-IC) in the presence of T cells or T cell supernatants. T cells were activated by anti-CD3/CD28 antibodies or in a mixed leucocyte reaction. IFN-α and other cytokines were determined in culture supernatants or patient sera with immunoassays. The effect of interleukin (IL) 3 and granulocyte-macrophage-colony-stimulating factor (GM-CSF) on pDCs was examined by the use of antibodies, and the expression of CD80/CD86 was determined using flow cytometry. Results: Activated T cells and supernatants from activated T cells increased IFN-α production by >20-fold. The stimulatory effect of T cell supernatants was reduced after depletion of GM-CSF (81%) or by blocking the GM-CSF receptor (55%–81%). Supernatant from activated T cells, furthermore, increased the frequency of CD80 and CD86 expressing pDCs stimulated with RNA-IC from 6% to 35% (p<0.05) and from 10% to 26% (p<0.01), respectively. Activated SLE T cells enhanced IFN-α production to the same extent as T cells from healthy individuals and a subset of patients with SLE had increased serum levels of GM-CSF. Conclusions: Activated T cells enhance IFN-α production by RNA-IC stimulated pDCs via GM-CSF and induce pDC maturation. Given the increased serum levels of GM-CSF in a subset of patients with SLE, these findings suggest that activated T cells may upregulate type I IFN production in SLE.